1989
DOI: 10.1172/jci113946
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia increases and hypercalcemia decreases the steady-state level of parathyroid hormone messenger RNA in the rat.

Abstract: To examine the effects of serum calcium concentrations on PTH biosynthesis, rats were made hyper-(serum total calcium, -3.5 mM) or hypocalcemic (-1.25 mM) and steadystate levels of PTH mRNA in parathyroid cells were measured by the primer extension method using a 32P-labeled synthetic oligomer. PTH mRNA levels increased about twofold in the rats made slightly hypocalcemic by infusion of calcium-free solution and decreased slightly in those made hypercalcemic by CaCI2 infusion (120-150 gmol/h) compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(49 citation statements)
references
References 17 publications
0
49
0
Order By: Relevance
“…High levels of extracellular Ca 2+ have been shown to promote intracellular PTH degradation both in vivo (5) and in vitro (4), thus an increase in intracellular PTH metabolism could be a major factor in the reduced PTH response to hypocalcemia found in Group II. Likewise, an elevation in extracellular Ca 2+ concentration has also been shown to inhibit PTH biosynthesis by decreasing levels of PTH mRNA (7,8). However, the decrease in PTH mRNA begins after 16 h of exposure to high Ca 2+ (7) ; therefore changes in PTH synthesis are probably not relevant in our acute (2 h) experiments.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…High levels of extracellular Ca 2+ have been shown to promote intracellular PTH degradation both in vivo (5) and in vitro (4), thus an increase in intracellular PTH metabolism could be a major factor in the reduced PTH response to hypocalcemia found in Group II. Likewise, an elevation in extracellular Ca 2+ concentration has also been shown to inhibit PTH biosynthesis by decreasing levels of PTH mRNA (7,8). However, the decrease in PTH mRNA begins after 16 h of exposure to high Ca 2+ (7) ; therefore changes in PTH synthesis are probably not relevant in our acute (2 h) experiments.…”
Section: Discussionmentioning
confidence: 85%
“…It is likely that some of the changes in PTH metabolism that have been described when parathyroid glands are exposed to acute hypercalcemia (4,5) will also be present in chronic hypercalcemia (6). Moreover, chronic hypercalcemia has been reported to influence PTH gene transcription and decrease PTH mRNA levels (7,8). Thus, theoretically, chronic hypercalcemia should also decrease the PTH response to hypocalcemia.…”
Section: Introductionmentioning
confidence: 99%
“…We (6, 8) and Yamamoto et al (7) have shown that a low serum calcium leads to marked increases in PTH mRNA levels. However, we have increased serum calcium by a number of methods for periods from 6 h to 3 wk and showed that a high serum calcium had no effect on PTH mRNA levels in vivo, despite serum calciums as high as 25 mg/dl (6, 30) although a modest effect of a calcium infusion for 48 h has been demonstrated (7).…”
Section: Discussionmentioning
confidence: 90%
“…This abnormality develops as a result of a combination of events, namely deficiency of 1,25-dihydroxycholecalciferol [1,25(OH) 2 D] (16,25), decreased expression of the vitamin D receptor (26) and the calcium-sensing receptor (27), hyperphosphatemia (28), hypocalcemia (29), and PTH resistance (30). In addition to these Figure 1.…”
Section: Discussionmentioning
confidence: 99%